2017
DOI: 10.1007/s00402-017-2631-0
|View full text |Cite
|
Sign up to set email alerts
|

Total hip arthroplasty after failed treatment of proximal femur fracture

Abstract: Performing THA after failed treatment of trochanteric fractures requires consideration of complication risk and incorrect femoral neck anteversion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 30 publications
0
19
0
1
Order By: Relevance
“…Abductor muscle insufficiency, trochanteric malunion, and the lack of restoration of vertical and lateral offset associated with dislocation are potential reasons for complications after salvage hip arthroplasty. [15,[18][19][20][21] Weaknesses of our study are the retrospective design and small sample size. A different feature of our study from others is that the mean age is >65 years in the literature, while the mean age of the patients in our group was 57 years.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Abductor muscle insufficiency, trochanteric malunion, and the lack of restoration of vertical and lateral offset associated with dislocation are potential reasons for complications after salvage hip arthroplasty. [15,[18][19][20][21] Weaknesses of our study are the retrospective design and small sample size. A different feature of our study from others is that the mean age is >65 years in the literature, while the mean age of the patients in our group was 57 years.…”
Section: Discussionmentioning
confidence: 96%
“…Franzén et al [20] noted greater risk in patients over 70 years of age, but noted that the complication rate was similar to that of primary THA for treatment of a collum femoris fracture. Recently, Tetsunaga et al [21] presented their research comparing the results of THA after failed pertrochanteric and collum femoris fractures, and they observed that THA after a failed collum femoris fracture had a lower complication rate. Abductor muscle insufficiency, trochanteric malunion, and the lack of restoration of vertical and lateral offset associated with dislocation are potential reasons for complications after salvage hip arthroplasty.…”
Section: Discussionmentioning
confidence: 99%
“…While our analysis was able to statistically validate the difference in the HHS, it failed to validate the differences in the rate of major orthopaedic complications during the first 2 years, most likely owing to the short follow-up. The long-term outcomes of CTHA or UTHA for patients with failed PFNA is a matter of great debate [22]. However, a growing but still very limited body of literature has investigated the therapeutic role of these two endoprostheses in the setting of failed PFNA and has suggested that the differences between CTHA and UTHA were attributed to errors in surgical techniques or indications [23].…”
Section: Discussionmentioning
confidence: 99%
“…4 This procedure has been shown to have high rate of complications such as intraoperative fracture and early dislocation. [5][6][7][8] However, the use of dual cup THR reduces the risk of postoperative dislocation following failed internal fixation of proximal femur fracture. 9 We present our midterm results of dual mobility (DM) THR in these high-risk patients.…”
Section: Introductionmentioning
confidence: 99%